Etiology and Short‐Term Outcomes of Upper Gastrointestinal Bleeding in Patients Presenting at the Emergency Department in a Tertiary Hospital in a Low Resource Setting–A Prospective Cohort Study - Nyantakyi Adu‐Darko; Solomon Gyabaah; Osei Yaw Asamoah; Tracey Afoley Laryea; Bright Oppong; Eileen Micah; Bernard Nkum (JGH Open)
ABSTRACT Background Upper gastrointestinal bleeding (UGIB) is one of the most common medical emergencies. Currently, there is a paucity of data on the clinical profile and outcome of UGIB in resource‐limited settings. Objective We aim to describe the etiology and outcomes of the patients who presented to the Emergency Department (ED) of a tertiary hospital in Ghana with UGIB. Methods This was a single‐center prospective cohort study involving 195 adults who presented with symptoms of UGIB from May 2022 to April 2023. Relevant baseline demographic and clinical characteristics were obtained. The cause of UGIB was determined as per findings at endoscopy. Patients were followed up for 6 weeks from admission, looking out for rebleeding, need for transfusion, length of hospital stay, and mortality. Results There were 145 (74.4%) males and 50 (25.6%) females, and the mean age ± SD was 51.4 ± 17.4 years. The main clinical presentations included melena (87.2%), hematemesis (69.7%) and postural dizziness (73.8%). The commonest findings at endoscopy were esophageal and gastric varices (33.3%), erosive gastritis and duodenitis (27.7%) and peptic ulcers (21.5%). The median length of hospital stay (IQR) was 7 days (5 days). 70.8% required whole blood transfusion with a median (IQR) of 2 units (2 units). The 6‐week mortality and rebleeding rates were 17.4% and 7.2%, respectively. Conclusion Variceal bleeding was the most common cause of UGIB at the emergency. One out of every fourteen patients that recover from acute UGIB may rebleed within the first six weeks one out of every six patients who present with acute UGIB may die within the succeeding six weeks.